ESL Students’ Perceptions of Error Correction Techniques in Oral Production: A Level-Based Approach - Zembyska, Maryna; Romanova, Yulia; Chumak, Nataliia (East European Journal of Psycholinguistics, 2022)
The article reveals the findings from a survey examining students’ perceptions of corrective feedback involving six groups of the first- through fifth-year ESL students enrolled in Bachelor’s and Master’s programs in English Language and Literature, Applied Linguistics, International Law, and International Communication and Global Media. The study attempts to reveal students’ perceptions of corrective feedback, as well as its perceived effectiveness and psychological relevance, which are analyzed on the basis of students’ answers. The aim of this survey-based research was to explore ESL students’ preferences for the amount and type of corrective feedback in speaking/reading and develop a method to help educators effectively choose the types of corrective feedback on the basis of their students’ level of English. In order to reinforce the study with substantial theoretical evidence, each type of corrective feedback was characterized on the basis of a rigorous review of related evidence-focused literature. The survey, which was administered to 78 ESL students at Taras Shevchenko National University of Kyiv and Khmelnytskyi National University, Ukraine, demonstrated a number of discrepancies in students’ preferences and attitudes. Their responses constituted grounds for assessing and ranking the prevalent verbal correction techniques in ESL teaching according to their perceived relevance. The implications of the current study could be taken into consideration by ESL teachers for determining an optimal set of error correction techniques in their own classrooms on the basis of their students’ level of English.